Peroxyl Radical Reactions in Water Solution: A Gym for Proton‐Coupled Electron‐Transfer Theories. Issue 23 (25th April 2016) - Amorati, Riccardo; Baschieri, Andrea; Morroni, Gloria; Gambino, Rossana; Valgimigli, Luca
Abstract: The reactions of alkylperoxyl radicals with phenols have remained difficult to investigate in water. We describe herein a simple and reliable method based on the inhibited autoxidation of water/THF mixtures, which we calibrated against pulse radiolysis. With this method we measured the rate constants k inh for the reactions of 2‐tetrahydrofuranylperoxyl radicals with reference compounds: urate, ascorbate, ferrocenes, 2, 2, 5, 7, 8‐pentamethyl‐6‐chromanol, Trolox, 6‐hydroxy‐2, 5, 7, 8‐tetramethylchroman‐2‐acetic acid, 2, 6‐di‐ tert ‐butyl‐4‐methoxyphenol, 4‐methoxyphenol, catechol and 3, 5‐di‐ tert ‐butylcatechol. The role of pH was investigated: the value of k inh for Trolox and 4‐methoxyphenol increased 11‐ and 50‐fold from pH 2.1 to 12, respectively, which indicate the occurrence of a SPLET‐like mechanism. H(D) kinetic isotope effects combined with pH and solvent effects suggest that different types of proton‐coupled electron transfer (PCET) mechanisms are involved in water: less electron‐rich phenols react at low pH by concerted electron‐proton transfer (EPT) to the peroxyl radical, whereas more electron‐rich phenols and phenoxide anions react by multi‐site EPT in which water acts as proton relay. Abstract : Radical kinetics : A simple and reliable method to measure the kinetics of peroxyl radical reactions in water is described (see figure). The proton‐coupled electron transfer from a variety of compounds was investigated. Electron‐poorer phenols react by concerted electron‐proton transfer (EPT or CPET), whereas electron‐richer phenols and phenoxide anions react by multi‐site EPT (separated CPET) in which water acts as proton relay, similarly to the chemistry of radical enzymes.